A expressão do sofrimento mental pela produção artística de homens encarcerados - Rayssa Gysele Teixeira da Silva; Miriane Virlane da Silva; Edla Maria da Silva; Wanda Maria Martins Medeiros; Eline Ferreira Mendonça (Universidade de Pernambuco, 2021)
Objective: Report the experience of using artistic production (clipping and collage) as a tool to express the mental suffering of prisoners. Methods: An experience report type study, carried out from the experience developed by a university extension project, aimed at men deprived of their liberty in a penitentiary unit in the Agreste of Pernambuco. Experience carried out in November 2019, with 26 participants. Results: The use of the tool enabled the representation and verbalization of anxieties intrinsic to prisoners, enabling the perception of the prevalence of feelings most present among them, their possible causes, and their potential risks to the mental health of the participants. Conclusion: The opportunity to make artistic productions was an effective strategy for identifying and analyzing possible indications of mental suffering, in addition to being a significant tool to guarantee humanization and legal rights.